EPIDEMIOLOGICAL CLINICAL PROFILE OF PATIENTS ATTENDED IN THE SURGICAL CLINIC OF A HOSPITAL OF THE ALTO SERTAO PARAIBANO : EPIDEMIOLOGICAL CLINICAL PROFILE OF PATIENTS ATTENDED IN THE SURGICAL CLINIC OF A HOSPITAL OF THE ALTO SERTAO PARAIBANO - Pereira, Maria Cecília; Medeiros, Renata Lívia Silva Fonsêca Moreira de; Silva, Talina Carla da; Alencar Neta, Raimunda Leite de; Feitosa, Ankilma do Nascimento Andrade; Oliveira, Geane Silva (Brazilian Journal of Production Engineering, 2020)
Objective: To trace the epidemiological clinical profile of patients undergoing surgical procedures in a hospital located in the high hinterland of Paraiba in 2017. Methodology: This is a documentary, observational, cross-sectional study using a quantitative approach. Data collection took place in a Hospital in the hinterland of Paraíba from August to October 2018, where 1018 records of patients who underwent different types of surgery were analyzed. Incomplete and illegible medical records were excluded. The data is stored in an electronic spreadsheet of the Microsoft Excel 2016 Program and later analyzed by the SPSS 21.0 program. Results: A large part of the procedures performed in the year 2017 was caused by trauma, and urgent orthopedic surgeries were performed, with reparative purpose. The prevalence was male with 613 (60.2%) patients and the hospitalization period ranged from 0-34 days (94%). Most of the consultations evolved without complications, however, 24 (2.4%) of the patients needed immediate intensive care and were transferred to the Intensive Care Unit and subsequently died and 23 (2.3%) needed hemoconcentrates. during the operation. Conclusion: Tracing the clinical and epidemiological profile will allow the planning of measures that help to reduce the risk of surgical complications. It is worth mentioning that the illegible medical records were a limitation for the study, in addition to the deficit of articles present in the literature.
Keywords: Epidemiology; Clinical; Surgical; Nursing